(untitled) (Research, Society and Development, 2020)
This paper aims to present the results obtained in the application of competences profile to undergraduated manager nurses in Nursing who work in the State of São Paulo using the statistical method of internal consistency evaluation. Methodological and descriptive study was used. This research was answered by 44 manager nurses and the competence profile had 62 statements in 3 domains of competence: educational, administrative and individual. The global Cronbach alpha was 0,909 for the educational domain, 0,897 for the administrative and 0,867 for the individual. The coefficient of variation was between 0,048 and 0,061. The Competence Profile has internal consistency classified as good and the coefficient of variation was good accuracy. The statistical interpretations that the competency profile was submitted guarantee its reliability for use by the scientific community.